2018
DOI: 10.1177/2050312118798941
|View full text |Cite
|
Sign up to set email alerts
|

The effect of far infrared radiation therapy on inflammation regulation in lipopolysaccharide-induced peritonitis in mice

Abstract: Objective:Far infrared radiation has been widely used in a variety of healthcare institutions and clinical research. Previous studies have shown that far infrared radiation can promote blood circulation and enhance the functioning of the immune system. Many patients receiving peritoneal dialysis have been co-treated with far infrared radiation to reduce the occurrence of inflammation. This study seeks to evaluate the effects of far infrared radiation therapy on inflammation.Method:We used the lipopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Exposure to FIR attenuates TNFα-induced adhesion molecule E-selectin, vascular cell adhesion protein-1, and monocyte chemoattractant protein-1 [55]. Recently, it was reported that exposure to FIR inhibits IL-6 and TNF-α, while activates eNOS expression and vascular endothelial function [56]. In addition, Chen et al (2016) showed that FIRmediated induction of eNOS is essential for improving endothelial function, which is essential for increases in Qa and AVFs [12,55].…”
Section: Preview Of Far-infrared Raymentioning
confidence: 99%
“…Exposure to FIR attenuates TNFα-induced adhesion molecule E-selectin, vascular cell adhesion protein-1, and monocyte chemoattractant protein-1 [55]. Recently, it was reported that exposure to FIR inhibits IL-6 and TNF-α, while activates eNOS expression and vascular endothelial function [56]. In addition, Chen et al (2016) showed that FIRmediated induction of eNOS is essential for improving endothelial function, which is essential for increases in Qa and AVFs [12,55].…”
Section: Preview Of Far-infrared Raymentioning
confidence: 99%
“…FIR energy in the form of heat is perceived in surrounding tissues by thermoreceptors in the skin [7]. Emerging studies have indicated that FIR therapy improves the health of patients with cardiovascular diseases, diabetes, inflammation, and other diseases [811]. However, these studies revealed only that FIR therapy has a protective effect on impaired vascular diseases; the underlying molecular mechanisms of the effects of FIR on eNOS/NO production have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies investigating nitric oxide synthase (NOS) activity and flap survival of the ischemic dorsum of rats demonstrated that FIR therapy also has a nonthermal biological effect on skin microcirculation (Gribbe et al, 2007). Constitutive NOS is important for basal blood flow in skin (Chang, 2018;Gribbe et al, 2007).…”
mentioning
confidence: 99%
“…FIR therapy is known to inhibit vascular inflammation (Chang, 2018;Yu et al, 2006) by inducing hemeoxygenase-1 (HO-1) synthesis (Lin et al, 2008), which leads to increased skin microcirculation and activates and restores endothelial nitric oxide synthase (eNOS; Gribbe et al, 2007;Yu et al, 2006), which regulates vascular tone and permeability. The therapy also inhibits interleukin (IL) 6 and tumor necrosis factor (TNF) a response to reduce vessel inflammation and increase angiogenesis (Lin et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation